On the Blow-up for Quasilinear Parabolic Equations (Journal of Partial Differential Equations, 1993)
This article is concerned with the position of blow-up points, blow up rate and an isoperimetric problem for the equation u_t = &#916u^m + u^p(p > m &#8805 1) in a convex bounded domain.
Keywords: Blow-up points; blow-up rate; isoperimetric problem